Urbanization Prospects in Asia: A Six-Country Comparison. (January 2013) - Rob, Ubaidur; Talukder, Md. Noorunnabi
Yet rural in nature, Asia is proceeding with a wide-ranging scale and fast pace of urbanization, resulting in accelerated economic growth. This article attempts a comparison on urbanization of six largest Asian countries: Bangladesh, China, India, Indonesia, Pakistan, and the Philippines. Among these countries, urban transition is underway in China, Indonesia, and the Philippines, which are also on track to mature as middle-income countries. India and Pakistan will soon graduate from low-income to lower-middle income countries, reaching the platform for faster urbanization with consequent economic growth. Regardless of the level of urbanization across countries, cities generate four-fifths of national income and the prominence of cities in generating country's national income is escalating. Still, urbanization primarily takes place through the development of large cities with surrounding industrial zones. Large cities will continue to play a significant role in absorbing future anticipated growth, but a decrease of growth rates in large cities is expected. Most of future city growth will occur in medium- and small-sized cities where existing coverage of basic public services is grossly inadequate, that entails greater concentration of power, investment, and services. To maximize the benefits of urbanization, countries need to judiciously plan the course of future urbanization—whether it should be a concentrated growth, a balanced growth, or a distributed growth.